2018
DOI: 10.1021/acs.biomac.8b01234
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Maltodextrin-Based Micelle/Hydrogel Composites for Simvastatin-Controlled Release

Abstract: Injectable hydrogels have shown great potential in bone tissue engineering. Simvastatin (SIM), a common hypolipidemic drug, has been suggested as a potential agent to promote bone regeneration. However, due to its hydrophobic nature, the compatibility between SIM and hydrogels is rather poor, thereby greatly affecting the drug release behavior, the mechanical properties, and dimensional stability of the hydrogels. Herein, we presented a novel design to entrap SIM in an injectable maltodextrin-based micelle/hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 45 publications
0
23
1
Order By: Relevance
“…For previously reported in vitro release studies, the loading amount of statin drugs per scaffold varies widely from 0.4 µg mL −1 to 10 mg mL −1 . [ 27–36 ] Regardless of the loading concentration, the reported SMV release from hydrogel scaffolds was much smaller amount and lasted shorter period compared to our results. For example, Yan et al.…”
Section: Resultscontrasting
confidence: 61%
See 2 more Smart Citations
“…For previously reported in vitro release studies, the loading amount of statin drugs per scaffold varies widely from 0.4 µg mL −1 to 10 mg mL −1 . [ 27–36 ] Regardless of the loading concentration, the reported SMV release from hydrogel scaffolds was much smaller amount and lasted shorter period compared to our results. For example, Yan et al.…”
Section: Resultscontrasting
confidence: 61%
“…[ 30 ] Some other studies loaded SMV in various hydrogels with 1–3 mg mL −1 concentrations (similar to our study), but drug release tests were carried in very small‐scale with diluted conditions and resulted only 0.4–1.0 µg of cumulative SMV release which completed within 30 days. [ 29,32 ] Although it is difficult to translate these results for the necessary dose of SMV in vivo, reported small animal studies indicated that 2–10 and 100–200 mg of SMV per scaffold seem to be effective concentrations in promoting bone regeneration for small and large bone defect models, respectively. [ 26 ] The extended delivery result in our large‐scale drug release study demonstrated feasibility of the hydrogel regeneration system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yan et al prepared micelle/hydrogel composites for the controlled release of simvastatin to achieve local bone regeneration ( Figure 1). 52 Composites of polymeric micro-or nanoparticles embedded in hydrogels may also facilitate the simultaneous delivery of multiple drugs with different solubility. This is important to enable combination therapy, which has shown several advantages compared to monotherapy such as reduced side effects 56 and lowering of drug resistance.…”
Section: Bio-based Composites Of Polymer Particles and Hydrogelsmentioning
confidence: 99%
“…Among these efforts, introduction of micelles, which undergo microscopic phase separation in aqueous environment, could consume the external loading to impart the hydrogels with higher resistance under big strain . Most importantly, the micelles also can work as carriers of biomolecules to realize controlled release, so to improve regeneration effect …”
Section: Introductionmentioning
confidence: 99%